الاتصال الرقمي وتأثيره على أداء الموظفين بالمؤسسة الجزائرية - دراسة ميدانية بمؤسسة الصندوق الوطني للتأمينات الاجتماعية للعمال الأجراء CNAS وكالة سوق أهراس - حمادة إيمان; كافي نور الهدى (My University, 2021)
Abstract This study aimed to identify the impact of digital communication on employee performance at the National Social Insurance Fund (CNAS) (Souk Ahras Agency) by linking it to work effectiveness and employee efficiency. Considering that digital communication has become one of the pillars upon which institutions rely to influence and improve employee performance, the study was based on a general question: What is the impact of digital communication on employee performance at the National Social Insurance Fund for Salaried Workers (CNAS) (Souk Ahras Agency)? This question led to two sub-questions. The first was: Does digital communication have an impact on work effectiveness at the National Social Insurance Fund (CNAS) (Souk Ahras Agency)? The second question was: Does digital communication have an impact on employee efficiency at the National Social Insurance Fund (CNAS) (Souk Ahras Agency)? The study relied on a set of methodological steps, using a social survey method with a sample, as the study falls within the category of descriptive studies. The questionnaire was used as the primary tool for collecting information. The study population consisted of all employees of the National Social Insurance Fund for Salaried Workers (CNAS) (Souk Ahras Agency), numbering 287 male and female employees. The study sample consisted of 57 male and female employees from various administrative levels, using a simple stratified random sample. The study concluded with several results, the most important of which are:  The National Social Insurance Fund for Salaried Workers (CNAS) (Souk Ahras Agency) applies digital communication in its various dimensions to varying degrees, and that there is a good level of job performance in the institution under study.  There is also a significant relationship between the use of digital communication and job performance at the level of work effectiveness and employee efficiency. We recorded the following: 1. Digital communication has a positive impact on the work efficiency of employees at the National Social Insurance Fund for Salaried Workers (CNAS) in Souk Ahras through:  Better time management.  Better achievement of goals.  Work organization.  Employee performance speed and accuracy.  Reducing time and effort.  Creating an atmosphere of comfort and stability for employees, encouraging them to take initiative and improve their performance throughout their career.  Eliminating errors in job performance. 2. Digital communication has a positive impact on the efficiency of employees at the National Social Insurance Fund for Salaried Workers (CNAS) in Souk Ahras through:  Creating a spirit of initiative and creativity.  Greater engagement in the work group.  Accuracy in work.  Creating employee responsibility.  Achieving desired goals.  Developing employee skills.  Completing tasks on time. -------------------------------- ملخص هدفت هذه الدراسة إلى تحديد أثر التواصل الرقمي على أداء الموظفين في الصندوق الوطني للتأمين الاجتماعي (CNAS) بوكالة سوق أهراس، من خلال ربطه بفعالية العمل وكفاءة الموظفين. ونظرًا لأن التواصل الرقمي أصبح أحد الركائز التي تعتمد عليها المؤسسات للتأثير على أداء الموظفين وتحسينه، فقد ارتكزت الدراسة على سؤال عام: ما أثر التواصل الرقمي على أداء الموظفين في الصندوق الوطني للتأمين الاجتماعي للأجراء (CNAS)؟ ويتفرع عن هذا السؤال سؤالان فرعيان: الأول: هل يؤثر التواصل الرقمي على فعالية العمل في الصندوق الوطني للتأمين الاجتماعي (CNAS)؟ والثاني: هل يؤثر التواصل الرقمي على كفاءة الموظفين في الصندوق الوطني للتأمين الاجتماعي (CNAS)؟ واعتمدت الدراسة على مجموعة من الخطوات المنهجية، باستخدام أسلوب المسح الاجتماعي بالعينة، حيث تندرج الدراسة ضمن الدراسات الوصفية. وتم استخدام الاستبيان كأداة رئيسية لجمع المعلومات. تكون مجتمع الدراسة من جميع موظفي الصندوق الوطني للتأمين الاجتماعي للأجراء (CNAS) (وكالة سوق أهراس)، والبالغ عددهم 287 موظفًا وموظفة. وبلغت عينة الدراسة 57 موظفًا وموظفة من مختلف المستويات الإدارية، باستخدام عينة عشوائية طبقية بسيطة.
Keywords: التواصل الرقمي، أداء الموظفين، الصندوق الوطني للتأمين الاجتماعي